لجان الصفقات العمومية في التشريع الجزائري - أميرة بن جاب الله; منال بن صافي (My University, 2022)
Summary: Public deals are defined as written contracts in the context of the legislation in force, concluded for a consideration with economic operators according to the conditions stipulated in this decree to meet the needs of the contracting authority in the field of works, supplies, services and studies, and since public deals have a direct relationship with public funds and the completion of major projects, they are promised an area prone to various forms of corruption and manipulation, and accordingly it is monitored through internal and external oversight bodies. In terms of internal control, it is carried out through the committee for opening envelopes and evaluating offers. As for external control, it is represented in committees at a local level and committees at a central level, and each elite has its composition and competencies that were created based on the recent presidential decree 247/15, which includes the regulation of public deals and mandates of the public utility. .................. الملخص: تعرف الصفقات العمومية على أنها عقود مكتوبة في مفهوم التشريع المعمول به تبرم بمقابل مع متعاملين اقتصاديين وفق الشروط المنصوص عليها في هذا المرسوم لتلبية حاجيات المصلحة المتعاقدة في مجال الأشغال واللوازم والخدمات والدراسات وبما أن للصفقات العمومية علاقة مباشرة بالأموال العامة وانجاز المشاريع الكبرى، فهي تعد بذلك مجالا معرضا لمختلف أشكال الفساد والتلاعب، وفقا لهذا تتم مراقبتها من خلال هيئات الرقابة الداخلية والخارجية. فمن حيث الرقابة الداخلية تتم عن طريق لجنة فتح الأظرفة وتقييم العروض، أما الرقابة الخارجية فتتمثل في لجان على مستوى محلي ولجان على مستوى مركزي. ولكل لجنة تشكيلتها واختصاصاتها التي استحدثت بناءا على المرسوم الرئاسي الأخير 247/15 المتضمن تنظيم الصفقات العمومية وتفويضات المرفق العام ......................... Résumé : Les transactions publiques sont définies comme des contrats écrits dans la notion de législation applicable conclus en retour avec des opérateurs économiques conformément aux conditions énoncées dans le présent décret pour répondre aux besoins de l’intérêt contractuel dans le domaine des travaux, fournitures, services et études. Étant donné que les transactions publiques sont directement liées aux fonds publics et à l’achèvement de grands projets en tant que tels, il s’agit d’un domaine d’exposition à diverses formes de corruption et de manipulation, surveillé en conséquence par des organismes de surveillance internes et externes.